A flavoprotein supports cell wall properties in the necrotrophic fungus Alternaria brassicicola. Issue 1 (December 2017) - Pigné, Sandrine; Zykwinska, Agata; Janod, Etienne; Cuenot, Stéphane; Kerkoud, Mohammed; Raulo, Roxane; Bataillé-Simoneau, Nelly; Marchi, Muriel; Kwasiborski, Anthony; N'Guyen, Guillaume; Mabilleau, Guillaume; Simoneau, Philippe; et al.
Abstract Background Flavin-dependent monooxygenases are involved in key biological processes as they catalyze a wide variety of chemo-, regio- and enantioselective oxygenation reactions. Flavoprotein monooxygenases are frequently encountered in micro-organisms, most of which require further functional and biocatalytic assessment. Here we investigated the function of theAbMak1 gene, which encodes a group A flavin monooxygenase in the plant pathogenic fungusAlternaria brassicicola, by generating a deficient mutant and examining its phenotype. Results Functional analysis indicates that the AbMak1 protein is involved in cell wall biogenesis and influences the melanization process. We documented a significant decrease in melanin content in the Δabmak1 strain compared to the wild-type and complemented strains. We investigated the cell wall morphology and physical properties in the wild-type and transformants using electron and atomic force microscopy. These approaches confirmed the aberrant morphology of the conidial wall structure in the Δabmak1 strain which had an impact on hydrophilic adhesion and conidial surface stiffness. However, there was no significant impairment in growth, conidia formation, pathogenicity or susceptibility to various environmental stresses in the Δabmak1 strain. Conclusion This study sheds new light on the function of a fungal flavin-dependent monooxygenase, which plays an important role in melanization.